Endoscopic entero-enteral bypass: an effective new approach to the treatment of postsurgical complications of hepaticojejunostomy - Mutignani, Massimiliano; Forti, Edoardo; Larghi, Alberto; Pugliese, Francesco; Cintolo, Marcello; Massad, Mutaz; Italia, Angelo; Tringali, Alberto; Ferrari, Giovanni Carlo; De Gasperi, Andrea; Rampoldi, Antonio; De Carlis, Luciano; Chiara, Osvaldo; Paparozzi, Carlo; Dioscoridi, Lorenzo (Endoscopy, 2019)
Background Management of biliary adverse events (BAEs) after biliodigestive anastomosis is challenging. We propose a new endoscopic approach to improve BAEs in this clinical setting.Methods Patients who had BAEs after a hepaticojejunostomy with Roux-en-Y loop or a Whipple procedure underwent creation of an entero-enteral endoscopic bypass (EEEB) between the duodenal/gastric wall and the biliary jejunal loop under endoscopic ultrasound (EUS) and fluoroscopic guidance using specifically designed fully covered self-expandable metal stents.Results 32 consecutive patients underwent EEEB, which was successful in all but one patient. One procedural and five long-term mild adverse events occurred. Endoscopic retrograde cholangiography (ERC) through the EEEB successfully treated all types of BAEs in these patients. Disease recurred in two patients who were successfully re-treated through the EEEB.Conclusions Our retrospective study showed that in patients with BAEs after biliodigestive anastomosis, EEEB is safe, feasible, and allows a successful long-term treatment of different BAEs in a tertiary referral center with high-level experience in both endoscopic retrograde cholangiopancreatography and EUS.